High-Dose Oral Vancomycin for Treatment of Clostridioides difficile Is Associated With High Risk of Subsequent Cultures With Gram-Negative Organisms. Issue 6 (25th November 2021) - Bader, Mazen S.; Someili, Ali; Alosali, Abdulmajeed; Hadzic, Amir; Irfan, Neal; Leto, Daniela; Mertz, Dominik; Brooks, Annie A.
Abstract : Background: Vancomycin is associated with disruption of the indigenous microbiota, potentially predisposing patients to overgrowth of endogenous pathogens. Our objective was to determine whether high-dose oral vancomycin is associated with cultures growing gram-negative organisms in adult patients with Clostridioides difficile infection (CDI). Methods: This is a retrospective cohort study of 632 adult patients with CDI from January 2015 to December 2017. The primary outcome was prevalence of cultures growing gram-negative organisms within 6 months after onset of the first episode of CDI. A multivariate logistic regression analysis was used to determine predictors of the outcome. Results: One hundred fifty-three patients (24.2%) had cultures growing gram-negative organisms after onset of CDI, where urine (97, 63.4%) and blood (27, 17.7%) were the most common sources. The most commonly isolated gram-negative organisms were Escherichia coli (49, 32.0%) and Klebsiella species (34, 22.2%). A total of 38 (38/100, 38.0%) and 48 (48/199, 24.1%) of the patients who received high- and standard-dose oral vancomycin, respectively, had gram-negative organism growth on culture (odds ratio [OR], 2.22, 95% confidence interval [CI], 1.41–3.5; P = 0.02). The multivariate analysis showed that high-dose oral vancomycin (OR, 2.21; 95% CI, 1.29–3.79; P = 0.004) and recent use of antibiotic therapy within 3 months (OR, 2.11; 95% CI, 1.27–3.52; P = 0.004) were associated with positive cultures growing gram-negative organisms. Conclusions: High-dose oral vancomycin therapy for CDI was associated with increased risk of gram-negative organisms probably throughout disruption of the indigenous microbiota.